2015
DOI: 10.1371/journal.pone.0125803
|View full text |Cite
|
Sign up to set email alerts
|

Defective Resensitization in Human Airway Smooth Muscle Cells Evokes β-Adrenergic Receptor Dysfunction in Severe Asthma

Abstract: β2-adrenergic receptor (β2AR) agonists (β2-agonist) are the most commonly used therapy for acute relief in asthma, but chronic use of these bronchodilators paradoxically exacerbates airway hyper-responsiveness. Activation of βARs by β-agonist leads to desensitization (inactivation) by phosphorylation through G-protein coupled receptor kinases (GRKs) which mediate β-arrestin binding and βAR internalization. Resensitization occurs by dephosphorylation of the endosomal βARs which recycle back to the plasma membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Phosphorylation of MYPT1 inactivates this key signalling event of calcium sensitization. We also demonstrated that endosomes from asthma‐derived HASM cells, as compared with non‐asthma HASM cells, manifest increased PI3Kγ activation and a reduction in protein phosphatase 2A activity that inhibits β 2 ‐adrenoceptor resensitization (Gupta et al , ). Collectively, these findings have implications providing a plausible hypothesis as to why β 2 agonists are less effective in Th2 airway inflammation (Duan et al , ; Aarthia et al , ; Townley, ).…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Phosphorylation of MYPT1 inactivates this key signalling event of calcium sensitization. We also demonstrated that endosomes from asthma‐derived HASM cells, as compared with non‐asthma HASM cells, manifest increased PI3Kγ activation and a reduction in protein phosphatase 2A activity that inhibits β 2 ‐adrenoceptor resensitization (Gupta et al , ). Collectively, these findings have implications providing a plausible hypothesis as to why β 2 agonists are less effective in Th2 airway inflammation (Duan et al , ; Aarthia et al , ; Townley, ).…”
Section: Discussionmentioning
confidence: 82%
“…The inflammatory milieu in asthma engenders AHR to contractile agonists and attenuates β 2 agonist‐induced bronchodilation (Cooper et al , ; Albano et al , ; Gupta et al , ). Previously, we showed that exposure to IL‐13 renders airways hyposensitive to β 2 ‐adrenoceptor agonist‐mediated airway dilation but not TAS2 receptor‐mediated airway dilation (Robinett et al , ).…”
Section: Discussionmentioning
confidence: 99%
“…PP2A is the most abundant serine/threonine phosphatase in mammals, and numerous studies show that its activity is reduced in asthma . PP2A activity was impaired in airway smooth muscle cells of asthmatics compared to nonasthmatics, in peripheral blood mononuclear cells from severe asthma patients and in animal models of steroid‐resistant AHR .…”
Section: Discussionmentioning
confidence: 99%
“…Increased activity of PI3K leading to the prevention of β2-receptor resensitization was found to be the main mechanism of β2-receptor dysfunction in these patients (Gupta et al, 2015).…”
Section: 1-evidence From Asthmatic Patientsmentioning
confidence: 85%